Comparison of basic direct torque control designs for permanent magnet synchronous motor - Kadir, M.N.A.; Mekhilef, Saad; Hew, W.P. (2007)
Basic PMSM-DTC drive controller consists of flux and torque hysteresis comparators and switching table. In the literature, three different designs have been reported. This paper investigates the three designs and compares their performance. The study aims to trace the reasons behind the recommendation of avoiding zero voltage states for PMSM-DTC reported in some studies. The system which avoids the zero states is compared with two systems include the zero states in their switching tables. The three systems are compared in their response time, switching losses, torque and flux ripples with three different input commands. The results as well as the theoretical discussion, show that the zero states should not be excluded from the switching table. The study concludes that the two level torque comparator, eight-state table design is suitable for two quadrant drives, while the three-level comparator, eight-state table is the most suitable for the four-quadrant drives.